2014
DOI: 10.1371/journal.pone.0094116
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Nerve-Sparing Radical Hysterectomy for Cervical Cancer: A Systematic Review and Meta-Analysis

Abstract: Backgroud and ObjectiveNerve-sparing radical hysterectomy (NSRH) may be associated with lower postoperative morbidity than radical hysterectomy (RH). We aimed to compare the clinical efficacy and safety of abdominal or laparoscopic NSRH and RH for treating cervical cancer through systematic review and meta-analysis.MethodsPubMed, EMBASE, The Cochrane Library and the Chinese National Knowledge Infrastructure databases were systematically searched for all relevant studies. Data were abstracted independently by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 36 publications
5
44
1
5
Order By: Relevance
“…After analyzing 8 studies reported urinary incontinence and 11 studies reported mean time of catheterization respectively, we found that NSRH could significantly decrease urinary incontinence and postoperative mean time of catheterization compared to RH. These results suggested that NSRH was an effective surgical technique with better postoperative bladder function than RH, which was in line with Long and colleagues' findings [33].…”
Section: Main Findingssupporting
confidence: 90%
“…After analyzing 8 studies reported urinary incontinence and 11 studies reported mean time of catheterization respectively, we found that NSRH could significantly decrease urinary incontinence and postoperative mean time of catheterization compared to RH. These results suggested that NSRH was an effective surgical technique with better postoperative bladder function than RH, which was in line with Long and colleagues' findings [33].…”
Section: Main Findingssupporting
confidence: 90%
“…Studies on the safety of NSRN are predominantly focused on the post-operative function of bladder and rectum and sexual activities, however, these studies have a number of limitations such as poor comparison, small sampling size, or shorter follow-up period. Whether NSRH is safer than the traditional radical hysterectomy has not yet been determined (32)(33)(34). Given that PNI of cervical cancer is associated with poor prognosis of cervical cancer patients, NSRH should be carefully recommended for cervical cancer patients with PNI.…”
Section: Discussionmentioning
confidence: 99%
“…The Tokyo method, developed originally by Ogino (1950) and revised by Kobayashi (1961) and Sakamoto and Takizawa (1988) demonstrated that the cardinal ligament is divided into two parts, the superficial or ventral "vascular part" as a target for ligation and removal and the deep or dorsal "nerve part" that should be preserved because it is likely to contain the pelvic splanchnic nerves. Many Western and Asian gynecologists seem to accept the Tokyo method as a standard method for nerve-sparing radical hysterectomy (2,3,7,16).…”
Section: Nerve-sparing Radical Hysterectomy -Technical Aspectsmentioning
confidence: 99%
“…He also demonstrated that pelvic splanchnic nerves runs along the most dorsal part of the cardinal ligament (3).…”
mentioning
confidence: 97%